Pengaruh Konservatisme Akuntansi, Leverage, Ukuran Perusahaan, Dan Penghindaran Pajak Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Sub Sektor Perdagangan Di Bursa Efek Indonesia Tahun 2019-2021 - Laurensya Monica; Kholidiah (INTELLECTUAL CAPITAL, Jurnal Akuntansi Kontemporer, 2024)
The purpose of this research is to examine and evaluate how accounting conservatism, leverage, company size, and tax avoidance affect a company's value. The research population was selected to be the manufacturing trade sub-sector companies listed on the Indonesia Stock Exchange in 2019–2021. Up to 85 businesses were used as research samples when data was collected. Purposive sampling is the data collection method used, and information is collected with special considerations tailored to the objectives or research problems. Multiple linear analysis is defined as the analytical method used in the written research. Data from the results of hypothesis testing show that tax avoidance has a negative impact on firm value, while leverage and firm size have a positive impact. Accounting conservatism has a limited impact on firm value, but all four factors can still influence it.